2018
DOI: 10.1016/j.comppsych.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety sensitivity and suicide risk among firefighters: A test of the depression-distress amplification model

Abstract: In the context of elevated depression symptoms, suicide risk is potentiated among firefighters reporting elevated AS cognitive and AS social concerns. Findings support and extend the depression-distress amplification model of suicide risk within a sample of firefighters. Interventions that successfully impact AS concerns may, in turn, mitigate suicide risk among this at-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“… Note : Suicide Behaviors Questionnaire‐Revised (Osman et al, 2001). The intent grouping was suggested based on Stanley et al (2018). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Note : Suicide Behaviors Questionnaire‐Revised (Osman et al, 2001). The intent grouping was suggested based on Stanley et al (2018). …”
Section: Resultsmentioning
confidence: 99%
“…However, as various studies suggested (Rogers & Joiner, 2019), TB‐7 could only predict PY‐SI above and beyond depression and anxiety, and it showed no incremental influence over and above PB. That said, when the risk group (i.e., LSB) (Osman et al, 2001) and the intent group (i.e., PLFS) (Stanley et al, 2018) were considered, the effect of TB‐7 was surfaced beyond depression and anxiety in the groups showing LSB and higher PLFS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite public perception that firefighters are a fit and healthy workforce, epidemiologic data suggest that firefighters suffer from a disproportionally high burden of cardiovascular disease, cancer, musculoskeletal injuries, and psychological distress (Daniels et al, 2014; Kales et al, 2007; Soteriades et al, 2011; Stanley et al, 2018). Studies have obeserved that cardiovascular disease has contributed to 45% of on duty fatalities, with firefighters experiencing an increased risk for a variety of cancers (Daniels et al, 2014; Lee et al, 2020).…”
mentioning
confidence: 99%